Peopling the Countryside: Roman Demography in the Albegna Valley and Jerba - Fentress, Elizabeth (Quantifying the Roman Economy: Methods and Problems, 2009)
The surveys of the Albegna Valley and the Island of Jerba were carried out respectively between 1979–1983 and 1995–2000 using similar methodologies (flow data and transect sampling). Each recovered over 1,000 sites, many of them Roman. They thus provide excellent comparable data for the study of ancient demographics. Using standard parameters, approximate densities per kilometre are calculated for each area, allowing the examination of change over time. The low figures for the Albegna Valley are then considered in the light of calculations regarding the population of Italy as a whole.
Keywords: Archéologie -- Djerba